Semi Fragile Watermark With Self Authentication And Self Recovery - Chaw Seng, Woo; Du, Jiang; Pham, Binh (Malaysian Journal of Computer Science, 2009)
Robust watermarks are suitable for copyright protection in a DRM scenario. On the other hand, fragile watermarks are good for tamper detection applications. Semi fragile watermarks possess some properties of both robust and fragile watermarks at a moderate level. The need for semi fragile watermarks arises from the requirements of content authentication where the watermark must highlight malicious attacks while tolerating legitimate changes that do not alter the content severely. Very few watermarking scheme has both self authentication and self recovery features. We developed and evaluated a semi fragile watermarking scheme that offers these features. The scheme embeds a downscaled version of an image into the image’s discrete wavelet transform subbands. Our scheme provides content authentication by allowing high quality JPEG compression, minor local distortion, and minimal noise insertion. Other changes such as histogram equalisation, cropping, rotation, and mean filtering are classified as malicious attacks because it affects the visual quality of the image. The scheme is practical because it does not require a reference image during content authentication. Tampered regions can be located correctly, and its original content can be recovered. The watermark information is secured by a secret key that randomises the watermark pixel positions. The single transform, correlator detector, and down-scaled processing spaces of the scheme offer low computational cost.